608 Optimising Return to Elective Total Hip Arthroplasty (THA) Following the COVID-19 Pandemic: Lessons Learned and Future Directions. (19th August 2022) - Paluch, A; Tariq, H; Small, O; Ratford, E; Sokolowski, S; Kassam, AA; Hubble, M; Howell, J; Charity, J; Gowda, S; Panteli, M; Wilson, M
Abstract: Aim: COVID-19 has led to unprecedented waiting times for elective surgery. Optimising patient pathways is paramount in tackling the backlog. Length of hospital stay (LOS) is an accepted surrogate for successful elective surgery. The aims of our study were: 1) report on changes in LOS after restarting our elective THA service; 2) identify barriers to early discharge, 3) investigate effectiveness of implemented changes. Method: A retrospective review of consecutive patients undergoing elective THA, comparing three groups: 1) enhanced care pathway (n=96; 09/2019–12/2019); 2) COVID group (n=56; 03/2021–04/2021); 3) intervention group (n=96; 05/2021–08/2021). Results: LOS in the enhanced care pathway group was 2.6 ±2.1 days. During initial resumption of elective operating (COVID group) the LOS was 4.8 ±4.5 days (statistically significant increase; p=0.011). Factors affecting LOS included reduced physiotherapy provision; lack of pre-operative occupational therapy review; loss of educational classes and worse pre-operative functional status. To address these our department employed three new physiotherapists, introduced training for nursing staff and created a post-operative proforma. The LOS subsequently reduced to 3.7 ±4.6days (p=0.166). Subgroup analysis of the intervention group showed age <75 (p<0.001) and ASA1–2 (p=0.036) were associated with reduced LOS (2.1±1.5 days). Other variables analysed did not significantly affect LOS. Conclusions: COVID-19 has had a significant effect on LOS, which is still not reversed. For effective resumption of THA services, pre-pandemic enhanced care pathways should be reinstated. With current restrictions preventing face-to-face classes, online educational sessions could be offered. Those younger than 75 years and ASA1–2 are most likely to be discharged without delay.